Contextual factors multiplex to control multisensory processes. Issue 1 (15th October 2015) - Sarmiento, Beatriz R.; Matusz, Pawel J.; Sanabria, Daniel; Murray, Micah M.
Abstract: This study analyzed high‐density event‐related potentials (ERPs) within an electrical neuroimaging framework to provide insights regarding the interaction between multisensory processes and stimulus probabilities. Specifically, we identified the spatiotemporal brain mechanisms by which the proportion of temporally congruent and task‐irrelevant auditory information influences stimulus processing during a visual duration discrimination task. The spatial position (top/bottom) of the visual stimulus was indicative of how frequently the visual and auditory stimuli would be congruent in their duration (i.e., context of congruence). Stronger influences of irrelevant sound were observed when contexts associated with a high proportion of auditory‐visual congruence repeated and also when contexts associated with a low proportion of congruence switched. Context of congruence and context transition resulted in weaker brain responses at 228 to 257 ms poststimulus to conditions giving rise to larger behavioral cross‐modal interactions. Importantly, a control oddball task revealed that both congruent and incongruent audiovisual stimuli triggered equivalent non‐linear multisensory interactions when congruence was not a relevant dimension. Collectively, these results are well explained by statistical learning, which links a particular context (here: a spatial location) with a certain level of top‐down attentional control that further modulates cross‐modal interactions based on whether a particular context repeated or changed. The current findings shed new light on the importance of context‐based control over multisensory processing, whose influences multiplex across finer and broader time scales. Hum Brain Mapp 37:273–288, 2016 . ©2015 Wiley Periodicals, Inc.